APLIKASI EDIBLE FILM KERAGINAN DAN Eucheuma sp. UNTUK MENGHAMBAT SUSUT BERAT BUAH ANGGUR HIJAU - Godras Jati Manuhara; Djagal Wiseso Marseno; Umar Santoso (Universitas Sebelas Maret, 2008)
Carrageenan extracted from Eucheuma sp. red algae has potential benefit to develop edible film. Eucheuma Sp. red algae used in this research were harvested from Pantai Selatan, a beatiful beach lies at Gunung Kidul resort, Jogjakarta Province, Indonesia. First objective of this research was proximat analysis of coarse-ground Eucheuma sp. red algae. Thirdly, weight loss analysis of green grapes wrapped by carrageenan edible film. Coarse-ground Eucheuma Sp. algae containde water, ash, protein, fat, and carbohydrate (by different) respectively 11,20%, 18,19%, 15,42%, 2,19% and 53,0%. Carrageenan extracted from Eucheuma sp. contained lower sulphuric (13,79%) than commercial carrageenan (Wako Chem.). Carrageenan edible film wrapping was not effective to reduce weight loss of green grapes.